Health Consequences of Nutrition in Childhood and Early Infancy - Tzee-Chung Wu; Po-Hon Chen (Pediatrics and Neonatology)
Medical and scientific studies have proven that the body's metabolic programming can be influenced by diet and nutrition from early infancy. As a result, the incidence and outcome of several metabolic diseases such as obesity, hypertension and cardiovascular disorders have been found to be associated with birth weight, growth and feeding patterns, and the body composition in early childhood. Exclusive or partial breast feeding for at least 6 months is recommended by the World Health Organization, while the European Society of Pediatric Gastroenterology Hepatology and Nutrition Committee on Nutrition recommends the introduction of complementary foods at 4–6 months of age. The fat content of the diet should not be below 25% of the energy intake in order to maintain ideal growth while dietary proteins above 15% of the energy intake is related to future obesity. Long term benefits of breast feeding include a more ideal serum lipid profile and blood pressure, improved neuro-cognitive scores, and a decreased incidence for atopic dermatitis in children who have family members with atopic diseases. Several studies have also acknowledged the long term benefits for neuro-cognitive development from certain nutrients including long-chain polyunstaturated fatty acids and docosahexaenoic acid. Meat intake has proved to be beneficial to psychomotor development. It is suggested that early introduction for complementary foods before 4 months of age is a risk factor for atopic dermatitis; while no strong evidence showed delaying weaning foods can decrease the risk for allergic diseases.